Galton's gleam Visual thinking and graphic discoveries. Issue 3 (27th May 2020) - Friendly, Michael; Wainer, Howard
Abstract : Michael Friendly and Howard Wainer recount the tale of Francis Galton and his discovery of weather patterns, which led to modern weather maps – providing a glimpse into the history of visual thinking and graphic communication, the subject of their new book Abstract : Michael Friendly and Howard Wainer recount the tale of Francis Galton and his discovery of weather patterns, which led to modern weather maps ‐ providing a glimpse into the history of visual thinking and graphic communication, the subject of their new book.